IMPACTO DE LA IMPORTACIÓN DE FERTILIZANTES SOBRE LA PRODUCCIÓN DE ARROZ EN LA PROVINCIA DE LOS RÍOS, ECUADOR. 2024 - JIMENEZ TOAZA ESTHER NURY (2025)
Rice producers in Los Ríos Province, Ecuador, depend heavily on fertilizers to maintain crop productivity. The objective is to determine how fertilizer imports impact agricultural production in Los Ríos Province. 2024. The type of research was descriptive and explanatory, using a quantitative approach. The study population was rice producers in Los Ríos Province during the year 2024, selecting a convenience sample of 120. The results showed that the exemptions from current tariff rates are not strengthening fertilizer import processes and that the logistical level of international fertilizer transport does not significantly benefit rice producers. It was possible to identify elements that present agricultural policies where the yield per hectare of current rice plantations is not managing to supply at least the domestic market of the country and that the low profitability in rice production is largely due to the limited reduction in production costs. It is concluded that the relationship between the variables Fertilizer Imports and Rice Production is significantly positive. The correlation obtained was Rho=0.808, which establishes a strong relationship between the variables and that the timely import of fertilizers, which impacts rice production levels in the province of Los Ríos, explains 65.29%. Keywords: Imports, fertilizers, production, rice.